The financial determinants of corporate cash holdings: evidence from growing firms - Gomes, Marília de Sena (2015)
Holding cash is a matter of managerial discretion. High growing firms face a very dynamic market competition. To maintain their competitive advantages those firms have to devote capital to new investment projects. Because these firms face a higher degree of asymmetry about the value of assets in place and future growth opportunities, this study contends that the entrenchment effect becomes less significant between managers and shareholders. Hence, this paper examines the financial determinants of corporate cash holdings in a sample of 231 French IPOs firms over the period 2000 to 2007. By using dynamic estimators, the results show that growing firms keep considerably higher cash ratios comparing with mature firms. In line with trade-off theory, growing firms follow an optimal level of cash holdings. Moreover, the results show that the adjustment of cash levels to their target level is faster than those found in previous studies. This faster adjustment could be synonymous of a higher business complexity which results in less information transparency, greater likelihood of financial distress and higher financial constraints costs. Furthermore, for firms that are more likely to suffer financial constraints, that is with low credit rating or the absence of them, cash flows and net working capital are seen a valid substitute of cash. Overall, the findings confirm that cash holdings of French IPOs firms increase (decrease) as the growth options climb (fall).